Clinicians' perspective on key domains in ANCA-associated vasculitis: a Delphi exercise. (4th March 2017) - Milman, N; Boonen, A; Tugwell, P; Merkel, PA; ,
Abstract : Objectives : The existing set of outcomes for anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) needs to incorporate views of outcome measure stakeholders to meet the current standards of outcome measurement proposed by the Outcome Measures in Rheumatology (OMERACT) initiative. This study identifies domains that clinical experts (one group of stakeholders) consider to be important to determining the impact of AAV using the International Classification of Functioning, Disability and Health (ICF), a framework that describes health along four components: body functions, body structures, activities and participation, and contextual factors. Method : An international group of clinicians with expertise in the clinical care of patients with vasculitis were identified through consultation with three major vasculitis societies. The relevant domains were determined using a three-round e-mail-based Delphi questionnaire. Results : Eighty-two clinicians were invited to participate in this study and 41 responded. Nineteen domains were identified as important by > 80% of participants: six body functions (energy, seeing, hearing, pain, respiratory, and renal function), seven body structures (peripheral nerves, eye, ear, nose, sinuses, lungs (and airways), and kidneys), three activities and participation (carrying out daily routine, remunerative employment, and recreation and leisure), and three environmental factors (medications, support and relationships, and health services, systems, and policies). Conclusions : Clinical experts focus on the physiological effects of AAV with less importance given to the effect of AAV on patients' activities and participation in life situations and the role of contextual factors. This study represents a step towards incorporating views of a range of stakeholders into disease assessment in AAV.